Transition experiences, intrapersonal resources, and job retention of new graduate nurses from accelerated and traditional nursing programs: A cross-sectional comparative study. (December 2017) - Read, Emily; Laschinger, Heather K.S.
Abstract: Background: With increasing numbers of new graduate nurses from accelerated nursing programs entering the workforce, it is important to understand their transition experiences, as they may differ from those of traditional graduates. Objectives: The aim of this study was to describe and compare the intrapersonal resources, transition experiences, and retention outcomes of these two groups. Design: A descriptive cross-sectional comparison study was conducted. Participants: A random sample of 3655 registered nurses with < 3 years of nursing experience were invited to participate from across Canada; 1020 responded (27.9%). The final sample included 230 nurses from accelerated programs and 768 from four-year programs (total n = 998). Methods: Following ethics approval, participants were mailed a questionnaire to their home address. One month later non-responders were sent a reminder letter, followed by a second questionnaire one month later (January to March, 2013). Descriptive statistics were conducted using SPSS. Group differences were assessed using independent samples t-tests for continuous variables and χ 2 tests for categorical variables. Results: Overall, there were few significant differences between new graduate nurses from accelerated and traditional programs. Nurses in both groups had high levels of intrapersonal resources, positive transition experiences, were satisfied with their jobs and their choice of nursing as a career, and their intentions to leave were low. Conclusions: All new graduate nurses need to have a strong educational preparation and transition support, regardless of their age and previous work and career experiences. Highlights: Graduates from accelerated and 4-year nursing programs were similar. In both groups the majority felt their nursing education had prepared them for practice. Accelerated program graduates were more likely to seek out additional training. Overall, new graduate nurses in our study were satisfied with their jobs and career choice. However, almost half would leave their current job for another specialty area.